Dynamics of Planktonic Prokaryotes and Dissolved Carbon in a Subtropical Coastal Lake - Schmitz Fontes, Maria Luiza; Dalpaz, Larissa; Tonetta, Denise; Antônio, Regina V.; Petrucio, Maurício (Frontiers in Microbiology, 2013)
To understand the dynamics of planktonic prokaryotes in a subtropical lake and its relationship with carbon, we conducted water sampling through four 48 h periods in Peri Lake for one year. Planktonic prokaryotes were characterized by the abundance and biomass of heterotrophic bacteria and of cyanobacteria (coccoid and filamentous cells). During all experiments, we measured wind speed, water temperature (WT), pH, dissolved oxygen (DO), precipitation, dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), and carbon dioxide (CO2). DOC was higher in the summer experiment (average = 465 μM - WT = 27°C) and lower in the winter experiment (average = 235 μM – WT = 17°C), with no significant variability throughout the daily cycles. CO2 concentrations presented a different pattern, with a minimum in the warm waters of the summer period (8.31 μM) and a maximum in the spring (37.13 μM). Daily trends were observed for pH, DO, WT, and CO2. At an annual scale, both biological and physical-chemical controls were important regulators of CO2. Heterotrophic bacteria abundance and biomass were higher in the winter experiment (5.60 x 109 cells L-1 and 20.83 μmol C L-1) and lower in the summer (1.87 x 109 cells L-1 and 3.95 μmol C L-1). Filamentous cyanobacteria (0.23 x 108 – 0.68 x 108 filaments L-1) produced up to 167.16 μmol C L-1 as biomass (during the warmer period), whereas coccoid cyanobacteria contributed only 0.38 μmol C L-1. Precipitation, temperature, and the biomass of heterotrophic bacteria were the main regulators of CO2 concentrations. Temperature had a negative effect on the concentration of CO2, which may be indirectly attributed to high heterotroph activity in the autumn and winter periods. DOC was positively correlated with the abundance of total cyanobacteria and negatively with heterotrophic bacteria. Thus, planktonic prokaryotes have played an important role in the dynamics of both dissolved inorganic and organic carbon in the lake.